Synonymische Beziehungen im Wortschatz and Wörterbucheinträge - Herberg, Dieter (HERMES - Journal of Language and Communication in Business, 1989)
By the example of synonymy the author shows requirements, possibilities and limits of representing macrostructural semantic relations of the vocabulary in a universal monolingual dictionary. The basis of the investigation are 10 common German-language dictionaries; the examples are all synonyms of the words Weltall and Weltraum. After showing the problem and the latest state of scientific research the author proposes to refer consequently to synonyms in the dictionary. Such a theoreticallly based method would enable the user of the dictionary to discover the synonymic relations which are concealed by the alphabetically arranged entries.